(untitled) (Dissertare, 2018)
The aim of this paper is to reflect about the African black heritage in Venezuela, as a contribution to the country’s culture. Regarding the methodological perspective, critical hermeneutics is adopted, as a method of argumentation and exegesis as an argumentative technique, to discuss three aspects that are part of the African legacy and that account for our cultural identity: the historical-social one, the religious one and the linguistic one. Regarding the historical and social legacy, the author comments on the participation of the African people in Venezuelan history, incorporating the idea of ​​"cimarronaje"; in attention to the magical-religious vision, it shows the thread of magic that surrounds the religious ideology of the black man; and on the subject of the linguistic legacy, it illustrates some terms of African origin that have remained in the current Spanish. The author concludes that to talk about the influence of black culture in Venezuela, we must discuss the multiple factors that influence the conformation of culture in this country, from diverse disciplinary visions and from cultural products of art, beyond the mere heritage or historical-anthropological legacy.